Long term toxicity and prognostic factors of radiation therapy for secreting and non-secreting pituitary adenomas - Rieken, Stefan; Habermehl, Daniel; Welzel, Thomas; Mohr, Angela; Lindel, Katja; Debus, Jürgen; Combs, Stephanie (Radiation oncology, 2013)
Radiotherapy is controversially discussed in the management of benign disorders for fear of late sequelae such as tumor induction. This study was initiated to investigate long-term toxicity, treatment outcome and prognostic factors after radiotherapy (RT) in patients with pituitary adenomas.
Gesehen am 12.01.2022